Social capital, individual responses to heat waves and climate change adaptation: An empirical study of two UK cities - Wolf, Johanna; Adger, W. Neil; Lorenzoni, Irene; Abrahamson, Vanessa; Raine, Rosalind (Global environmental change, 2010)
It has been claimed that high social capital contributes to both positive public health outcomes and to climate change adaptation. Strong social networks have been said to support individuals and collective initiatives of adaptation and enhance resilience. As a result, there is an expectation that social capital could reduce vulnerability to risks from the impacts of climate change in the health sector. This paper examines evidence on the role social networks play in individuals’ responses to heat wave risk in a case study in the UK. Based on interviews with independently living elderly people and their primary social contacts in London and Norwich, we suggest that strong bonding networks could potentially exacerbate rather than reduce the vulnerability of elderly people to the effects of heat waves. Most respondents interviewed did not feel that heat waves posed a significant risk to them personally, and most said that they would be able to cope with hot weather. Bonding networks could perpetuate rather than challenge these narratives and therefore contribute to vulnerability rather than ameliorating it. These results suggest a complex rather than uniformly positive relationship between social capital, health and adaptation to climate change.